The influence of meaning on the perception of speech sounds - Kazanina, Nina (National Academy of Sciences, 2006)
As part of knowledge of language, an adult speaker possesses information on which sounds are used in the language and on the distribution of these sounds in a multidimensional acoustic space. However, a speaker must know not only the sound categories of his language but also the functional significance of these categories, in particular, which sound contrasts are relevant for storing words in memory and which sound contrasts are not. Using magnetoencephalographic brain recordings with speakers of Russian and Korean, we demonstrate that a speaker’s perceptual space, as reflected in early auditory brain responses, is shaped not only by bottom-up analysis of the distribution of sounds in his language but also by more abstract analysis of the functional significance of those sounds.